Une construction des immigrants musulmans : La mosquée, un espace des communautés musulmanes au Japon - Keiko Sakurai (Revue des Mondes Musulmans et de la Méditerranée)
Estimates of the number of non-Japanese Muslims residing in Japan in 2004 range from 60 to 70,000 people, an estimated 80 to 90% of the Japanese Muslim population. Among foreign residents from Islamic countries, the largest single country of origin is Indonesia, followed by Pakistan, Bangladesh, Iran, Nigeria, Turkey and Egypt a majority of whom began settling in Japan in the early 90s. Non-Japanese Muslims live in various parts of Japan and do not form ethnic communities. Accordingly, Muslims living in Japan tend to go to the mosque closest to their homes or workplaces. Those who live in metropolitan areas have some options and choose a mosque based on their ethnic or sectarian preferences. Even so, the number of mosques remains limited and mosques in Japan are competitive multi-ethnic and multi-lingual spaces where Muslims of different background compete to prove themselves. Confronted with a diversity of interprÉtations and practices of Islam, some faithful have become doctrinaire in their beliefs, others have become more tolerant. International networks also play a role in the development of mosques in that they provide access to fundamentalist preachers, missionary groups and foreign donations. Á comparative evaluation of Mosques in Japan will allow us to better understand the role of Mosques both as places of worship and as communitarian spaces.